Analysis of ways to solve the problems of accounting and valuation of fixed assets in ukraine during the war and in the post-war period - Havrys, Mykola O.; Havrys, Oleksandr M.; Tkachenko, M. O. (ВНЗ "Національна академія управління", 2024)
The war in Ukraine has created significant challenges in accounting and valuing fixed assets, crucial for businesses and economic recovery. These problems include the destruction and damage of assets, legaluncertainties, depreciation complexities, inflation, andshortages ofskilledprofessionals. Solving these issues during the war andthe post-war periodis essentialfor stabilizing the economy and facilitating recovery. To address asset destruction due to military actions, standardized protocols for damage assessment should be adopted. A National War Damages Register can help document and assess the extent oflosses, which will also be needed for determination ofthe amount ofthe future reparations from the aggressor. Currently, after more than two years of full-scale war, the International Register ofDamages from russian aggression has been created in 2024, to which only slightly more than 10,000 applications from the affected parties have been submitted so far, although their expected number is from 6 to 10 million. The National War Damages Register has not yet been created. Insurance policies for wartime risks and government-backed compensation mechanisms are vital for mitigating losses. Temporary legal frameworks should be established to guide businesses on assetwrite-offs, depreciation, andtaxation during the war. Flexible tax policies, such as deferredpayments for affected businesses, can ease the financial burden. Post-war legal reforms will also be necessary to address these challenges retrospectively. Clear guidelines must be introduced to account for war-damaged assets, allowing businesses to apply impairment testing and accurately report the value ofdamagedor destroyedassets. Businesses shouldalso have the option to suspenddepreciation for idle assets to avoid overstating expenses. Asset relocations due to war should be documented through digital asset management systems to track and account for moved assets. Government subsidies and financial assistance can help businesses manage relocation costs, ensuring minimal financial disruptions. Assets seized by occupying forces should be recorded as losses in financial statements. International legal mechanisms should be pursued to seek compensation, and accounting standards should allow for recognition oflosses due to expropriation. To combat the effects ofinflation, inflation-adjusted accounting should be implemented, allowing businesses to maintain accurate valuations. Regular revaluations based on current market conditions will help businesses manage inflationary impacts on their asset values. The war has led to a shortage ofaccountants and auditors. Temporary support from international accounting organizations and remote auditing solutions can help bridge this gap. Additionally, training programs should be developed to increase the supply of qualified financial professionals for the post-war recovery period. Addressing these challenges is crucial for business continuity, transparency, and economic recovery in Ukraine. Implementing government-led initiatives, leveraging international support, and updating legal frameworks will ensure that businesses can manage their fixed assets effectively during and after the war. These solutions are essential for long-term recovery, helping Ukraine rebuild its economy and infrastructure.

Війна в Україні створила значні проблеми в обліку та оцінці основних засобів, що є критично важливими для бізнесу та економічного відновлення. Ці проблеми включають знищення та пошкодження активів, правову невизначеність, складність амортизації, інфляцію та брак кваліфікованих фахівців. Вирішення цих проблем у воєнний та післявоєнний період є важливим для стабілізації економіки та сприяння відновленню. Для вирішення проблеми знищення активів унаслідок військових дій слід прийняти стандартизовані протоколи оцінки збитків. Національний Реєстр Збитків від війни може допомогти задокументувати та оцінити розмір збитків, що також знадобиться для визначення розміру майбутніх репарацій від агресора. Наразі, після більш ніж двох років повномасштабної війни, у 2024 році створено Міжнародний Реєстр Збитків від російської агресії, до якого поки що подано лише трохи більше 10 тис. заяв від постраждалих сторін, хоча очікувана їх кількість – від 6 до 10 мільйонів. Національний Реєстр Збитків поки що не створений. Страхування ризиків військового часу та державні механізми компенсації є життєво важливими для зменшення збитків. Необхідно створити тимчасові правові рамки, які скеровували бізнес в питаннях списання активів, амортизаціїта оподаткування під час війни. Гнучка податкова політика, наприклад відстрочка платежів для постраждалих підприємств, може полегшити фінансовий тягар. Післявоєнні правові реформи також будуть необхідні для ретроспективного вирішення цих проблем. Слід запровадити чіткі вказівки щодо обліку пошкоджених війною активів, що дозволить підприємствам застосовувати тестування на знецінення та точно звітувати про вартість пошкоджених або знищених активів. Підприємства також повинні мати можливість призупинити амортизацію незадіяних активів, щоб уникнути завищення витрат. Переміщення основних засобів через війну має бути задокументовано за допомогою цифрових систем управління активами для відстеження та обліку таких активів. Державні субсидії та фінансова допомога можуть допомогти підприємствам з витратами на переїзд, забезпечуючи мінімізацію пов’язаних з цим фінансових проблем. Активи, захоплені окупаційними військами, повинні реєструватися як збитки у фінансовій звітності. Необхідно використовувати міжнародні правові механізми для отримання компенсації, а стандарти бухгалтерського обліку повинні дозволяти визнання збитків через експропріацію. Для боротьби з наслідками інфляції слід запровадити облік з поправкою на інфляцію, що дозволить підприємствам підтримувати точні оцінки. Регулярна переоцінка на основі поточних ринкових умов допоможе підприємствам впоратися з впливом інфляції на вартість їхніх активів. Війна призвела до дефіциту кваліфікованих бухгалтерів і аудиторів. Тимчасова підтримка від міжнародних бухгалтерських організацій і рішення для дистанційного аудиту можуть допомогти подолати цю прогалину. Крім того, необхідно розробити навчальні програми для збільшення кількості кваліфікованих фінансових спеціалістів у післявоєнний період відновлення. Вирішення цих проблем має надзвичайно важливе значення для безперервності бізнесу, прозорості та економічного відновлення України. Реалізація урядових ініціатив, залучення міжнародної підтримки та оновлення законодавчоїбази забезпечать підприємствам можливість ефективного управління своїми основними активами під час і після війни. Ці рішення необхідні для довгострокового відновлення, допомагаючи Україні у відбудові економіки та інфраструктури.
Аналіз шляхів вирішення проблем обліку та оцінки основних засобів в україні під час війни та у післявоєнний період
Keywords: accounting offixed assets; valuation offixed assets; analysis ofproblems; ways to solve the problems ofaccounting offixed assets; war and post-war period; flexible accounting standards; government compensation; government incentives; облік основних засобів; оцінка основних засобів; аналіз проблем; шляхи вирішення проблем обліку основних засобів; воєнний та післявоєнний період; гнучкі стандарти обліку; державна компенсація; державне стимулювання